If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.12(12) + 0.03 = 0.06(12 + x) Multiply 0.12 * 12 1.44 + 0.03 = 0.06(12 + x) Combine like terms: 1.44 + 0.03 = 1.47 1.47 = 0.06(12 + x) 1.47 = (12 * 0.06 + x * 0.06) 1.47 = (0.72 + 0.06x) Solving 1.47 = 0.72 + 0.06x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.06x' to each side of the equation. 1.47 + -0.06x = 0.72 + 0.06x + -0.06x Combine like terms: 0.06x + -0.06x = 0.00 1.47 + -0.06x = 0.72 + 0.00 1.47 + -0.06x = 0.72 Add '-1.47' to each side of the equation. 1.47 + -1.47 + -0.06x = 0.72 + -1.47 Combine like terms: 1.47 + -1.47 = 0.00 0.00 + -0.06x = 0.72 + -1.47 -0.06x = 0.72 + -1.47 Combine like terms: 0.72 + -1.47 = -0.75 -0.06x = -0.75 Divide each side by '-0.06'. x = 12.5 Simplifying x = 12.5
| -3(6p+5)-2(5-17p)-3(1+5p)=0 | | 4y+60=180 | | 6+5n-3=5n+18-3n | | 7(x-3)-3x+1=4(x-5) | | x=2(6)+-4 | | x=-2/3(4)+3 | | 3(7x-2)+2(8-4x)-4(3x+1)=-3 | | 2(3x-1)=5-x-3 | | (x^4-1)/(x^3)=0 | | (x^4-1)/(x^3) | | x+(1/x)=(17/4) | | x-8/3=12 | | 2(n+4/3)=12 | | X/6=x/7-14 | | y=-2(x-4)(x+1) | | 3/4=3m/4 | | -6+(-3)-5+7+(-4)= | | 4x(2)+3x+6=(2)7x-2+2x+4 | | 32=5+3t | | 3y-11y= | | 12x+13=31+3x | | 40x+5.5x=529 | | 3b-6-5b-4= | | -16t^2+88t+8=0 | | 2x+9-x=8-(3x-6) | | 0.6u+2.1=4.5 | | -8=22t-6r^2 | | (5x+8)+(x-3)=33 | | x+x+9000=54000 | | -19/3(-3b/19)=19/3(27/19) | | -9x^2+30x-35=0 | | 5[12-(6-3a)]-2a=2(1-a) |